Evolutionary conservation of leptin effects on wound healing in vertebrates: Implications for veterinary medicine - Reeve, Robyn E.; Quale, Kyla; Curtis, Grace H.; Crespi, Erica J. (Frontiers in Endocrinology, 2022)
In mammals, the cytokine hormone leptin promotes wound healing by increasing inflammation, cellular recruitment, angiogenic regrowth, and re-epithelialization; however, it is not known whether leptin has conserved actions on wound healing in other vertebrates. Here, we tested the hypothesis that leptin promotes both the quality and speed of wound healing in the South African clawed frog, Xenopus laevis. First, fluorescent immunohistochemistry using a polyclonal antibody specific to Xenopus leptin showed that in juvenile dorsal skin, leptin protein is expressed in the dorsal epidermal layer, as well in blood vessel endothelial cells and sensory nerves that run along the base of the dermis. Injection of recombinant Xenopus leptin (rXleptin) stimulates phosphorylated STAT3 (pSTAT3), indicative of leptin-activated JAK/STAT signaling in the epidermis. Similar to mammals, leptin protein expression increases at the wound site after injury of the epidermis. We then cultured “punch-in-a-punch” full-thickness dorsal skin explants in three doses of rXleptin (0, 10, and 100 ng/ml) and showed that leptin treatment doubled the rate of wound closure after 48 h relative to skin punches cultured without leptin. Food restriction prior to wound explant culture reduced the amount of wound closure, but leptin injection prior to euthanasia rescued closure to similar control levels. Leptin treatment also significantly reduced bacterial infection of these epidermal punches by 48 h in culture. This study shows that leptin is likely an endogenous promoter of wound healing in amphibians. Leptin-based therapies have the potential to expedite healing and reduce the incidence of secondary infections without toxicity issues, the threat of antibiotic resistance, or environmental antibiotic contamination. The conservation of leptin’s actions on wound healing also suggests that it may have similar veterinary applications for other exotic species.